An Assessment of Injection Practices in Urban Health Centers of Surat City: Are the Health Care Workers Safe? - Ashish Naik; Vaibhav Gharat; R.K. Bansal (Medsci Publications, 2012)
Background: Healthcare workers in developing countries inconsistently practice universal precautions and are commonly exposed to blood in the course of their work via needle-stick injuries and direct contact. Aims and Objective: The present study was carried out to provide comprehensive data from assessment of injection practices in a Surat city with an overall aim to compare the differences between knowledge and practices among health care providers. Methodology: Qualitative study design, consisted of assessing the knowledge of staff nurses and observation during injection procedure, took place over a 2 month period during June-July 2011 in 20 health centres of Surat Municipal Corporation area. A semi-structured questionnaire regarding their views and experiences related to injection practices, awareness about the different diseases spread by faulty injection technique and disposal of biomedical waste was asked. Results: The total of 40 staff nurses was involved in the study. All of them knew that gloves should be wore during injection procedure but only 14 (35 %) were actually wearing it. Only 6 (15 %) of participants knew that gloves should be wore for both personal and patient safety. Around 65 % of the participants felt that needle should not be recapped after giving injection but 50 % were actually found to be recapping it. The percentage of needle stick injury among nurses came to be 65 %. Around 90 %, 80 % and 30 % of the participants feels that hospital staff can acquire HIV/AIDS, Hepatitis B and Hepatitis C infection respectively but 10 (25 %) don't know anything about how this disease can contract to the health staff. Conclusion: There was a great disparity between knowledge and practice of health care workers regarding injection practices. Efforts are needed to be done in this regard for the benefit of both health care worker and patients.